Polish oeuvre" in N. Leskov’sprose - Neminuszczij, Arkadij (Acta Polono-Ruthenica, 2006)
The present article regards the specificity of the realization of the Polish theme in N. Leskov’s prose. This element of the Russian writer’s artistic world is represented in his writing of the 1860s-1880s. N. Leskov had a personal experience of Poland which he visited at the beginning of the 1860s. Most vividly Polish thematics is represented in the novel Nowhere (1864), as well as in the stories and articles of his last years: Russian Democrat in Poland (1880), Interesting Men (1885), etc.The realization of the Polish motif in N. Leskov’s prose is, on the one hand, traditional for Russian literature, depicting international phenomena and topos of different cultures as „other” which are seldom perceived as foreign and hostile. The individuality of N. Leskov is manifested in the fact that his version of depicting Poland and Polish is opposed to the official state imperial position according to which Poland was regarded as a permanent source of danger. This stereotype is destroyed in N. Leskov’s prose.